Application of Problem-Based Learning Model (PBM) in Improving Indonesian Language Learning Achievement for Class IX.J Students of SMP Negeri 2 Kendari - La Ode Sudu (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
The purpose of the study was to describe the application of the Problem-Based Learning (PBM) model in Indonesian subjects in class IX.J of SMP Negeri 2 Kendari. This type of research is qualitative and quantitative research. The method used in this research is the descriptive method. The research instrument is a test of student learning outcomes and observation. The factors studied were the characteristics of students, teachers, and learning resources. Procedures for collecting data using classroom action research (CAR): (1) planning, (2) implementation, (3) observation and evaluation, and (4) reflection. CAR out in two cycles. Data were collected by observing the activities of teachers and students during the learning process in order to apply the problem-based learning model (PBM) using observation sheets. The mastery or understanding of the material the teacher has taught can be measured through tests given to students at the end of each lesson. The results showed that the problem-based learning model (PBM) application in Indonesian subjects in class IX.J SMP Negeri 2 Kendari has been running effectively. During the learning process, the teacher has fulfilled the specified components, starting from the planning stage to reflection. Applying the problem-based learning model (PBM) can improve student achievement in class IX.J SMP Negeri 2 Kendari.